City, countryside, and the spatial organization of value in classical antiquity - Rosen, Ralph Mark.; Sluiter, I. (Mnemosyne, Supplements, 2006)
The third in a series that explores cultural and ethical values in Classical antiquity, this volume examines the dichotomy between 'city' and 'country' in ancient Greek and Roman cultures. Fourteen papers address a variety of topics on this theme, and include a variety of methodological approaches-archaeological, iconographic, literary and philosophical. The book demonstrates that, despite a common rhetoric of polarity in antiquity that tended to construct city and countryside as very distinct, oppositional categories, there was far less consistency (and far more nuance) about the ideologies felt to inhere in each.